Analisis Penerapan Standar Akuntansi PSAK 4 dalam Pengungkapan Laporan Keuangan Konsolidasi - Indarti, Wanti; Damayanti, Novia; Uzliawati, Lia (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
This research was conducted by the author with the aim of finding out several important aspects related to PT Perusahaan Kertas Tjiwi Kimia Tbk, especially matters that focus on share ownership analysis and disclosure of consolidated financial statements in accordance with the provisions of Statement of Financial Accounting Standards 4 (Revised 2009). The research method used in this research is a qualitative approach with the application of descriptive and comparative analysis techniques. Through this approach, an in-depth understanding is obtained regarding the level of compliance of PT Perusahaan Kertas Tjiwi Kimia Tbk with PSAK 4 in preparing consolidated financial statements, including disclosure of share ownership, net profit, interest expense, dividend distribution and the company's overall financial performance. . The analysis results obtained in this research show that the company has complied with the standards set out in PSAK 4. In this context, the consolidated financial statements presented by PT Perusahaan Kertas Tjiwi Kimia Tbk can be considered to meet the accounting requirements and standards applicable in Indonesia.